2019
DOI: 10.1038/s41598-019-48086-4
|View full text |Cite
|
Sign up to set email alerts
|

Diet-related selectivity of macroplastic ingestion in green turtles (Chelonia mydas) in the eastern Mediterranean

Abstract: Understanding the drivers of key interactions between marine vertebrates and plastic pollution is now considered a research priority. Sea turtles are primarily visual predators, with the ability to discriminate according to colour and shape; therefore these factors play a role in feeding choices. Classification methodologies of ingested plastic currently do not record these variables, however here, refined protocols allow us to test the hypothesis that plastic is selectively ingested when it resembles the food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 55 publications
0
19
2
1
Order By: Relevance
“…No difference in dietary composition was found among sections (Supplementary Material S3). Due to the bias towards hard-bodied intestinal content and elevated digestion state precluding correct identification, the intestines were excluded from all analyses except the analysis of macroplastics ingestion with size, as they are often found in the largest quantities here (Matiddi et al 2017) and persist in a non-degraded state (Clukey et al 2017;Duncan et al 2019). As no differences were found in dietary composition between gut sections, the oesophagus and stomach were subsequently combined for all further analyses.…”
Section: Gut Content Sample Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…No difference in dietary composition was found among sections (Supplementary Material S3). Due to the bias towards hard-bodied intestinal content and elevated digestion state precluding correct identification, the intestines were excluded from all analyses except the analysis of macroplastics ingestion with size, as they are often found in the largest quantities here (Matiddi et al 2017) and persist in a non-degraded state (Clukey et al 2017;Duncan et al 2019). As no differences were found in dietary composition between gut sections, the oesophagus and stomach were subsequently combined for all further analyses.…”
Section: Gut Content Sample Collection and Analysismentioning
confidence: 99%
“…Interaction with fisheries is a leading cause of mortality of marine turtles worldwide (Lewison et al 2014), and differing habitat use among demographic groups has been shown to influence susceptibility to some fishing techniques (Wallace et al 2008;Casale 2011;Snape et al 2013). Monitoring these responses to environmental change along with others, such as exposure to plastic ingestion (Duncan et al 2019) and arrival and monitoring of invasive species (Özdilek et al 2015), can be achieved through long-term dietary studies. Indeed, marine turtles are now used as bio-indicators for monitoring plastic pollution across the Mediterranean Sea through gut contents analysis (INDICIT Consortium 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that marine megafauna ingest plastic for a number of reasons, including (1) mistaking the visual characteristics of the item for food (Gregory 2009, Schuyler et al 2012, 2014b, Hoarau et al 2014, Duncan et al 2019b; (2) mistaking the odor of biofouled plastic as food (Pfaller et al 2020); (3) accidentally, through non-selective feeding strategies such as filter feeding (Besseling et al 2015) or if otherwise mixed with natural food items (Di Beneditto & Awabdi 2014); (4) if the item is attached to or covered with natural prey (Frick et al 2009); or (5) via trophic transfer from con taminated prey (Nelms et al 2018).…”
Section: Ingestionmentioning
confidence: 99%
“…Arcangeli et al (2019) analyzed a 5‐year time series of sea turtle and marine litter observations along transects in the Mediterranean Sea to detect seasonal overlap and assess exposure risk, though results indicated species and floating litter observations were variable even along fixed transects. Duncan, Arrowsmith, et al (2019) conducted a study to test whether green turtles in the eastern Mediterranean selectively ingest debris that resembles dietary items, and found selectivity toward certain types, colors, and shapes of plastic (e.g., sheets and threads; black, clear, and green items; linear shapes) which may signal selection of items similar to sea grass, a main dietary item. The authors believe more investigation is necessary, but did find a significant negative relationship between turtle size and the number and mass of ingested plastic pieces, implying shifts in diet over time.…”
Section: Effects Of Microplastic Debrismentioning
confidence: 99%